2016
DOI: 10.1590/1678-457x.05416
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, sensory and nutritional characteristics of cereal bars with addition of acacia gum, inulin and sorbitol

Abstract: The cereal bars are products globally accepted and consumed by all age groups. In this study, by Response Surface Methodology (RSM), the effects of different concentrations of inulin, acacia gum and sorbitol in the characteristics of hardness, color and water activity of cereal bars were studied. A total of 17 experiments being 8 factorials, 6 axials and 3 repetitions at the central point were performed. The regression model presented for the hardness was significant indicating that the quantities of inulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 10 publications
7
22
2
3
Order By: Relevance
“…On the present study, snack bars presented moisture content according to the value established by FDA (Food and Drug Administration) for cereal flours and related products (< 15%) (Food and Drug Administration, 2017). The same trend was observed by Gutkoski et al (2007) who developed oat based snack bars and obtained moisture content ranging from 10.75 to 13.95% and also by Srebernich et al (2016) who reported moisture content ranging from 13.36 to 13.50% in snack bars developed from rice and oat flakes added with acacia gum, inulin, and sorbitol.…”
Section: Proximate Composition Of Freshly Prepared Snack Barssupporting
confidence: 82%
“…On the present study, snack bars presented moisture content according to the value established by FDA (Food and Drug Administration) for cereal flours and related products (< 15%) (Food and Drug Administration, 2017). The same trend was observed by Gutkoski et al (2007) who developed oat based snack bars and obtained moisture content ranging from 10.75 to 13.95% and also by Srebernich et al (2016) who reported moisture content ranging from 13.36 to 13.50% in snack bars developed from rice and oat flakes added with acacia gum, inulin, and sorbitol.…”
Section: Proximate Composition Of Freshly Prepared Snack Barssupporting
confidence: 82%
“…The b* the value for potato extrudates energy bars is between 8.87 to 16.62 which is much lower than this study (Gir and Mridula, 2016). In addition, based on Srebernich et al (2016), the b* values obtained in their cereal bars (with the addition of acacia gum, inulin, and sorbitol) are ranges between 22.36 to 28.03, which is quite similar to this study. In another study, the b* values ranged from 20.21 to 40.23, where the protein bar enriched with Spirulina plantensis was used as samples (Kumar et al, 2018).…”
Section: Colour Profile Analysissupporting
confidence: 79%
“…The soakingmicrowave energy bar has the higher a* value (6.53) suggesting that the sample has more red colour than the others; whereas the lower a* value is 4.81 when using soaking-boiling process. Based on a study by Srebernich et al (2016), the results showed a* values ranging from 7.60 to 11.93 higher than this analysis for their cereal bars. They convinced that the variation of a* and b* value in their samples are due to the level of potato extrudates and sweeteners used in the formulation.…”
Section: Colour Profile Analysiscontrasting
confidence: 49%
“…We analyzed the potential of Hydrogen (pH), Titratable Acidity (TA), moisture, ash, lipids, proteins, Soluble Solids (SS), lactose, carbohydrates, and energy [7,8] of the substrates (WM, SM, and BS) as well as that of the fermented beverages produced via kefir's interaction With Whole Milk (KW), Skim Milk (KS), and Water With Brown Sugar (KB).…”
Section: E T H O D S Preparation Of Beverages and Chemical Analysismentioning
confidence: 99%